Design of in situ Solid-State NMR Rotor Inserts and Their Application to Catalytic Reactions - SHEN Xueyuan; WANG Ruichen; QI Guodong; XU Jun; DENG Feng (Chinese Journal of Magnetic Resonance)
In situ solid-state nuclear magnetic resonance (NMR) serves as a powerful means to study catalytic reactions under operating conditions. Standard solid-state NMR rotors typically struggle to match the pressure and temperature of active reactions during sampling. Here, we introduce specialized inserts for commercial solid-state NMR rotors capable of withstanding pressures from atmospheric to 618.3 kPa and temperatures ranging from room temperature up to 433 K. With this innovative design, we examine the isomerization of dihydroxyacetone (DHA) on Sn-MFI zeolite catalyst using in situ 1H MAS NMR, revealing the presence of a gem-diols-type intermediate during the transformation of DHA into glyceraldehyde.